Inflation Targeting in Korea : An Empirical Exploration - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 1999)
The revised Bank of Korea Act states that the primary goal of monetary policy is price stability, suggesting that monetary policy will move toward an inflation-targeting framework. The paper explores some of the practical aspects of this move, including such issues as the predictability of inflation, the definition of the price index, the inflation target's time horizon, and the width of the inflation-target bands. On balance, the empirical evidence suggests that Korea is likely to be successful in adopting an inflation-targeting framework over the medium term.